Volume 8: Microturbines, Turbochargers and Small Turbomachines; Steam Turbines 2016
DOI: 10.1115/gt2016-56518
|View full text |Cite
|
Sign up to set email alerts
|

Structural Optimization of Fir-Tree Root and Groove for Turbine Blade With Splines and Genetic Algorithm

Abstract: The wide use of fir-tree root and groove in turbine structures prompts the expectation to find optimum configurations, which ensure that stresses are in the safe limits to avoid mechanical failure. To perform the optimization, the reasonable characterization of root configuration is required. The existing researches characterized the fir-tree root with straight line, arc or even elliptic fillet, then the parameters of these features were defined as design variables to perform root profile optimization. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…There are articles in the literature that deal with the optimization of the fir tree root joint geometry with the objective of reducing the stresses in the joint. [16][17][18][19][20][21] Random errors in manufacturing process introduce variability in the geometry of the blade root and the disk slots. Due to the variability in blade and disk geometry within the tolerance limits, the contact area at joints could be higher or lower than that of the nominal design geometry.…”
Section: Background and Motivationmentioning
confidence: 99%
See 3 more Smart Citations
“…There are articles in the literature that deal with the optimization of the fir tree root joint geometry with the objective of reducing the stresses in the joint. [16][17][18][19][20][21] Random errors in manufacturing process introduce variability in the geometry of the blade root and the disk slots. Due to the variability in blade and disk geometry within the tolerance limits, the contact area at joints could be higher or lower than that of the nominal design geometry.…”
Section: Background and Motivationmentioning
confidence: 99%
“…Random forest methods have been applied with varying degree of success to regression and classification problems arising in different fields ranging from fluid flow modeling 29 to medical prognosis. 17 Ling and Templeton 30 investigated the use of three different data-driven algorithms including RF and support vector machines 31 to identify regions in a fluid flow where the inaccuracy of Reynolds-averaged Navier-Stokes (RANS) models is high. They concluded that data-driven algorithms provide a substantial improvement over conventional RANS error detection methods and showed the performance of RF to be superior compared with that of the other algorithms used.…”
Section: Background and Motivationmentioning
confidence: 99%
See 2 more Smart Citations
“…In the second step, after identifying the most sensitive design variables, several optimization methods such as the NSGA-II non-dominated sorting genetic algorithm, Downhill Simplex and an evolutionary optimization algorithm were used and compared. Deqi Yu et al, 7 used the Multi-island genetic algorithm in order to obtain the optimal fir-tree root with better stress distributions and low stress concentrations. A single objective Genetic Algorithm (GA) was used by Alinejad et al, 8 in order to find the optimum fir-tree shape having minimum von-Mises stress.…”
Section: Design Optimization Frameworkmentioning
confidence: 99%